A double-edged sword. Issue 3 (September 2020) - Vandebotermet, Martijn; Staels, Frederik; Giovannozzi, Simone; Delforge, Michel; Tousseyn, Thomas; Steelandt, Thomas; Corveleyn, Anniek; Meyts, Isabelle; Maertens, Johan; Yserbyt, Jonas; Schrijvers, Rik
A 33-year old man presented because of progressive fatigue, loss of appetite and malaise for 2 months. While carrying out his job as a baggage handler at the airport, he noticed exertional dyspnoea (New York Heart Association class II) with a slight nonproductive cough. There was no weight loss or fever, although he mentioned paroxysmal hot flushes. There were no recent infections and his past medical and familial history were negative. The patient denied the use of drugs, nicotine or alcohol, reported no recent travel and had a stable relationship. In medicine, not everything is what it seems and sometimes you need all the pieces of the puzzle in order to complete the diagnosis. This is a case of a disease with two different faces and a review of its respiratory impact. https://bit.ly/2SDKwE5